PENGARUH PARTISIPASI ANGGOTA SEBAGAI PEMILIK DAN ANGGOTA SEBAGAI PENGGUNA TERHADAP PEROLEHAN SISA HASIL USAHA (SHU) BAGI ANGGOTA PADA KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) KANTOR BUPATI KAMPAR - Wiza Melia Sari; Suarman '; RM. Riadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The aims of the study is to know the level of participation of members either as owner or as a user and effect to the acquisition (SHU) for members of KPRI Kantor Bupati Kampar. The subject of this study is the members of KPRI Kantor Bupati Kampar, amount 84 people, the samples are taken by using proportional sampling. The data are primary data and secondary with data collection by using questionaires and documentation. The technique of analisis data I used is Multiple Linear Regression Anaysis Processed through SPSS 21 for Windows and Microsoft Excel program. Based on the analysis concluded that the significant value on the table annova obtained F count amounted to 0,000 critical values less than of 0,05. Then obtained 0,000 < 0,05, and these result show that participation of members as owner and members as a user together affect the acquisition (SHU)of KPRI Kantor Bupati Kampar. while partially variable participation of members as owner has a significant level amounted to 0,026 < 0,05 the results show that the participation of members as owner has effect on SHU . The variable participation as a user has a signigicant level amounted to 0,000 < 0,05 the results show that the participation of members as a user has effect on SHU. Judging from R square 0f 0,343 this show that the effect of an independent variable on the dependent variable amounted to 34,3% while the rest 65,7% influenced by other variables not examined. Keyword : Cooperatives, member participation, the balance of the enterprises, SHU